Development of Animated Videos on Pasta Material as Learning Media for Class - Nenden Mayang Arum Ratna Sari; Atat Siti Nurani; Ade Juwaedah (Media Pendidikan Gizi dan Kuliner, 2023)
Research on the development of animated video learning media on pasta material has objectives including: (1) developing animated video learning media on pasta material in the Food Processing and Presentation subject; (2) determine the suitability of the results of the animated pasta video product based on the assessment of validators consisting of material experts, language experts and media experts. The method in this research is research and development (RD) with a 4D development model (define, design, develop and disseminate) which is limited to the development stage with expert appraisal or validation by material experts, language experts and media experts. Data collection was carried out by means of interviews, literature studies and expert validation sheets. The results obtained from this research are: (1)The animated video media for pasta material in the Food Processing and Serving subject was developed through three stages including the define, design and develop stages. (2) The results of the feasibility of the pasta material animation video based on the expert appraisal validation process by material experts, language experts and media experts stated that it was suitable for use as a learning medium